Effect of Advanced Age on Off-pump Coronary Artery Bypass Grafting - Zhang, Renteng; Jiang, Hui; Wang, Huishan; Yang, Zhonglu; Zhou, Nan; Gao, Hao (The Thoracic and Cardiovascular Surgeon, 2016)
Objective To investigate the perioperative features of aged patients undergoing off-pump coronary artery bypass grafting (OPCABG) surgery, and identify the perioperative effect of advanced age on OPCABG.Method A total of 61 aged patients and 585 younger patients from August 2013 to June 2014 were enrolled in this study. The perioperative features were summarized, and the effects of advanced age on intraoperative variables, as well as the postoperative complications were identified using logistic regression analysis.Results The anastomosis time of the target coronary artery and intraoperative dosage of vasoconstrictor drugs was significantly longer or higher in the aged patients. The incidence of the postoperative complications, such as atrial fibrillation, repetitive mechanical ventilation, gastrointestinal dysfunction, and renal insufficiency, were significantly higher in the aged patients. The intubation time and postoperative hospital stay were significantly longer in the aged patients. No significant difference was found between the two groups in cardiocerebrovascular accident and mortality. Multivariate logistic regression analysis revealed advanced age was the independent risk factor for coronary artery anastomosis time, vasoconstrictor dosage, repeated mechanical ventilation, atrial fibrillation, gastrointestinal dysfunction, as well as the intubation time and hospital stay.Conclusion OPCABG in aged patients was safe and effective for avoiding a significant increase for cardiocerebrovascular accident and mortality. Relatively, the tolerance of aged heart to stimulation was poor. Atrial fibrillation, repetitive mechanical ventilation, and gastrointestinal dysfunction were more likely to occur in aged patients. Advanced age made intubation time and hospital stay prolonged significantly.
Keywords: aged population; coronary heart disease; coronary artery bypass grafting; perioperative complication